Pengaruh Lingkungan Kerja Terhadap Semangt Kerja Pegawai Kantor Camat Wawo Kabupaten Bima - Abdul Arif; Muhammad Yusuf; Jaenab Jaenab (Indo Publishing, 2026)
This study aims to examine the influence of the work environment on the work morale of employees at the Wawo District Office, Bima Regency. An associative research design was employed. The study population consisted of 40 employees at the Wawo District Office, Bima Regency, comprising 14 Civil Servants (PNS), 16 Government Employees with Work Agreements (P3K), and 10 honorary staff members. Data analysis using SPSS indicates that the work environment (X1) influences the work morale of employees at the Wawo District Office, Bima Regency.